Monetary policy and structural changes in Colombia, 1990-2016: A Markov Switching approach (2018)
This paper analyzes the Colombian economic context between 1990Q1-2014Q4, using a Markov-Switching Dynamic Stochastic General Equilibrium Model (MS-DSGE) to identify regime switches in the driven mechanisms of the economy. Bayesian methods are applied, allowing for changes in the monetary policy rule, nominal rigidities, and shock volatilities of the model. The results support evidence of shifts in the structural parameters of several equations that define the dynamics of the economy. The best fit specification of the MSDSGE model allows for independent switches in the Taylor rule, parameters, coefficients of the domestic Phillips curve, and changes in volatilities. Estimations from the DSGE model suggest a regime switching in monetary policy from a low to high inflation response, which coincides with the adoption of inflation targeting in 1999Q3, and with a lower Phillips curve slope in the Economy since 1998Q3. Historical decomposition analysis and counterfactual exercises show that regime switches were crucial when the Central Bank adopted an Inflation Targeting regime, and, by themselves, these regime changes could be interpreted as disinflationary shocks. These phenomena are not identifiable when using linear models.